Capacity-limited resources are used for managing sensory degradation and cognitive demands: Implications for age-related cognitive decline and dementia. (December 2020) - Billig, Adam R.; Feng, Nicole C.; Behforuzi, Hura; McFeeley, Brittany M.; Nicastri, Casey M.; Daffner, Kirk R.
Abstract: Older adults with sensory deficits are at higher risk for developing cognitive impairment and dementia. It remains uncertain if the link between sensory and cognitive functioning reflects a common underlying factor or whether sensory deficits directly undermine cognitive processing. This issue was addressed by comparing behavioral and event-related potential responses of 16 older and 16 young adults during a working memory paradigm that parametrically varied visual contrast level (100%, 69%, 22%) and cognitive task load (1–4 face pairs to remember). The groups were well-matched on demographic and neuropsychological variables; however, older adults had worse corrected visual acuity and contrast sensitivity. The study's major finding was an interaction between visual contrast level and task load on performance accuracy (percent of correct responses) and the allocation of resources for decision making/updating (as indexed by the P3b amplitude). The negative impact of degraded visual processing was greater at higher levels of task demand. This result suggests that a shared pool of processing resources is used to mediate cognitive operations and manage the processing of degraded images. The study also demonstrated that older adults reach the limits of their processing capacity at lower levels of task load. The interaction between visual degradation and task demand, accompanied by the age-related reduction in available processing resources highlight the increased vulnerability of older adults. Specifically, an age-associated decline in visual acuity and contrast sensitivity puts older adults at risk for depleting their limited resources in the service of processing degraded visual images. The results of this study underscore the potential importance of optimizing vision in older adults to help mitigate age-associated cognitive decline.